STRATEGI METODE DAKWAH MELALUI PROGRAM FILANTROPI: STUDI KASUS LAZISNU MWCNU PALANG TUBAN - Kris Fitriana Wahyu Lestari, Siti; Rifqi Ali Maghfur Pratama, Muhammad (ASWALALITA: Journal of Da'wah Management, 2024)
Da'wah through philanthropic programs is a method used to convey the message of Islam by approaching the social conditions of society. Philanthropic programs have great potential to create sustainable social change while strengthening relations between Muslims, especially the Nahdlatul Ulama (NU) community. One concrete example of the application of da'wah through philanthropy can be found in the programs implemented by the Nahdlatul Ulama Zakat, Infaq and Shadaqah Institution (LAZISNU) MWCNU Palang. This study aims to analyze the da'wah strategy implemented through various philanthropic programs, such as giving zakat, infaq, and sedekah, which are distributed to people in need. Through a qualitative approach, this study identifies how LAZISNU MWCNU Palang utilizes philanthropic activities as a means to introduce inclusive Islamic values and rahmatan lil 'alamin, and has an impact on social change in the Palang sub-district. In addition, community involvement in LAZISNU MWCNU Palang's philanthropic activities is a forum for spreading Islam effectively.